The Effect of Pharmaceutical Care against Patient Loyalty with Intervening Variables of Patient Satisfaction at "X" Pharmacy, Sukoharjo Regency - Fransiskus Xaverius Sulistiyanto Wibowo Sutardjo; Amor Sofandi; Novi Elisa (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aimed to determine whether there was an effect of pharmaceutical care on patient satisfaction, to find out whether there was an effect of pharmaceutical care on patient loyalty and to find out whether there was an effect of patient satisfaction in partially mediating the relationship between pharmaceutical care and patient loyalty. Data analysis obtained from testing was carried out by knowing whether there was an effect or not carried out by statistical tests, Anova test using the SPSS 16th version. The results showed that pharmaceutical care had a positive effect on patient satisfaction (sig 0.000 <0.05), pharmaceutical care had a positive effect on patient loyalty (sig 0.000 <0.05), patient satisfaction had a positive effect on patient loyalty (sig 0.000 <0.05), and patient satisfaction has an effect in partially mediating the relationship between pharmaceutical care and patient loyalty (sig 0.000 <0.05).